Biostoning of textile effluent with laccase enzyme - Iqbal, K; Nadeem, A; Zafar, U (Bangladesh Journal of Scientific and Industrial Research, 2021)
The incessant release of textile effluent comprehending dyes and heavy metals which impacts on aquatic life. Current study used an enzyme to eradicate phenolic compounds and synthetic dyes from textile effluent by an indigenously isolated white rot fungus Pleurotus ostreatus- P1 has been cultured and indicated the utmost laccase activity with synthetic medium; as reacting substrate for dye decolorization. The textile effluent decolorization optimization has been conducted with different concentrations of laccase enzyme, temperature and pH. The 90% effluent decolorization was obtained by applying response surface methodology (RSM) conditions temperature, crude laccase enzyme and pH, 25˚C, 13.5 U/ml and 5 respectively. The predicted values were validated with experimental values, that confirms the steadiness of the model. Bangladesh J. Sci. Ind. Res.56(2), 115-124, 2021